Community-based prevalence of rheumatic heart disease in rural Ethiopia: Five-year follow-up - Gemechu, Tadesse; Parry, Eldryd H. O.; Yacoub, Magdi H.; Phillips, David I. W.; Kotit, Susy (PLOS Neglected Tropical Diseases, 2021)
Background As little is known about the prevalence and clinical progression of subclinical (latent) rheumatic heart disease (RHD) in sub-Saharan Africa, we report the results of a 5 year follow-up of a community based, echocardiographic study of the disease, originally carried out in a rural area around Jimma, Ethiopia. Methods Individuals with evidence of RHD detected during the baseline study as well as controls and their family members were screened with a short questionnaire together with transthoracic echocardiography. Results Of 56 individuals with RHD (37 definite and 19 borderline) in the original study, 36 (26 definite and 10 borderline) were successfully located 57.3 (range 44.9–70.7) months later. At follow-up two thirds of the definite cases still had definite disease; while a third had regressed. Approximately equal numbers of the borderline cases had progressed and regressed. Features of RHD had appeared in 5 of the 60 controls. There was an increased risk of RHD in the family relatives of borderline and definite cases (3.8 and 4.0 times respectively), notably among siblings. Compliance with penicillin prophylaxis was very poor. Conclusions We show the persistence of echocardiographically demonstrable RHD in a rural sub-Saharan population. Both progression and regression of the disease were found; however, the majority of the individuals who had definite features of RHD had evidence of continuing RHD lesions five years later. There was an increased risk of RHD in the family relatives of borderline and definite cases, notably among siblings. The findings highlight the problems faced in addressing the problem of RHD in the rural areas of sub-Saharan Africa. They add to the evidence that community-based interventions for RHD will be required, together with appropriate ways of identifying active disease, achieving adequate penicillin prophylaxis and developing vaccines for primary prevention.